New approaches to social protection: microinsurance - Markus Loewe (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
Microinsurance has become a very popular concept in the international development debate. It is an arrangement whereby the members pool their risks, but at contribution levels that even people on low and fluctuating incomes can afford. This concept can be realised for life and disability insurance and even, under certain conditions, for pension insurance and insurance that gives protection against the effects of the weather and natural disasters, provided that professional insurers assume responsibility for product design and risk management, but cooperate in product marketing and customer servicing with agents who operate close to target groups, such as self-help groups, non-governmental organisations and cooperatives. Health and liability insurance, on the other hand, can be offered only with substantial limitations. Microinsurance schemes help to close the gap that the informally employed often face in the overall set of social protection schemes in developing countries. Compared to social insurance, however, they are only a second-best solution and should be used primarily when the state is unable or unwilling to extend social insurance coverage to informal-sector employees. In no case are they a substitute for social transfer schemes that support the extremely poor.
Keywords: 330